MMG22 Potently Blocks Hyperalgesia in Cisplatin-treated Mice. (15th April 2023) - Cataldo, Giuseppe; Lunzer, Mary M.; Akgün, Eyup; Wong, Henry L.; Portoghese, Philip S.; Simone, Donald A.
Highlights: The bivalent ligand MMG22 consists of a MOR agonist and mGluR5 antagonist. MMG22 reduced mechanical hyperalgesia produced by cisplatin in mice. MMG22 reduced hyperalgesia without tolerance. MMG22 may produce antinociception through the formation of a MOR-mGluR5 heteromer. Abstract: MMG22 is a bivalent ligand containing MOR agonist and mGluR5 antagonist pharmacophores connected by a 22-atom linker. Intrathecal (i.t.) administration of MMG22 to inflamed mice has been reported to produce fmol-range antinociception in the reversal of LPS-induced hyperalgesia. MMG22 reduced hyperalgesia in the spared nerve injury (SNI) model of neuropathic pain at 10 days after injury but not at 30 days after injury, perhaps related to the inflammation that occurs early after injury but subsequently subsides. The present study determined the efficacy of MMG22 in cisplatin-treated male mice in order to provide data relating to the efficacy of MMG22 in the treatment of neuropathic pain that is associated with inflammation. Groups of eight mice each received daily intraperitoneal (i.p.) injections of cisplatin for seven days to produce robust mechanical allodynia defined by the decrease in withdrawal threshold using an electronic von Frey applied to the plantar surface of the hind paw. Intrathecal administration of MMG22 potently reduced mechanical hyperalgesia (ED50 0.04 fmol/mouse) without tolerance, whereas MMG10 was essentially inactive. Morphine was less potent than MMG22 by >5-orders of magnitude and displayed tolerance. Subcutaneous MMG22 was effective (ED50 = 2.41 mg/kg) and devoid of chronic tolerance. We propose that MMG22 induces the formation of a MOR-mGluR5 heteromer through selective interaction with the upregulated NR2B subunit of activated NMDAR, in view of the 4600-fold reduction of i.t. MMG22 antinociception by the selective NR2B antagonist, Ro25-6981. A possible explanation for the substantially reduced potency for MMG22 in the SNI model is discussed.